The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4238/2015.february.6.16
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs of resistance to white mold in common bean from multiple markers by using Bayesian analysis

Abstract: ABSTRACT. In this study, we identified simple sequence repeat, amplified fragment length polymorphism, and sequence-related amplified polymorphism markers linked to quantitative trait loci (QTLs) for resistance to white mold disease in common bean progenies derived from a cross between lines CNFC 9506 and RP-2, evaluated using the oxalic acid test and using Bayesian analysis. DNA was extracted from 186 F 2 plants and their parental lines for molecular analysis. Fifteen experiments were carried out for phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…In a study developed by Lara et al (2014Lara et al ( , 2015, ME1 was found to be located 0.82 and 0.29 cM from a QTL with 71.37 and 0.55% heritability by the straw test and oxalic acid evaluation methods, respectively. This QTL acts to increase resistance to white mold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study developed by Lara et al (2014Lara et al ( , 2015, ME1 was found to be located 0.82 and 0.29 cM from a QTL with 71.37 and 0.55% heritability by the straw test and oxalic acid evaluation methods, respectively. This QTL acts to increase resistance to white mold.…”
Section: Discussionmentioning
confidence: 99%
“…Haggard (2007) identified this marker associated with resistance to white mold by straw test in GL6. By using both the straw test and reaction to oxalic acid, Lara et al (2014Lara et al ( , 2015 used the mapping population obtained from a cross between CNFC 9506 and RP-2 and identified the markers BM184 and BM187 associated with the most significant QTL, with high heritability. However, these markers contribute to reduce resistance and are distant from each other at 43.84 cM by the oxalic acid method.…”
Section: Discussionmentioning
confidence: 99%
“…DNA extraction was done according to the method used by Lara et al (2015). Nucleic acids were rehydrated in Tris/EDTA buffer and quantified on 1% agarose gel using DNA markers of known concentrations.…”
Section: Progeny Genotypingmentioning
confidence: 99%
“…In addition to the complexity of the white mold resistance, wide variability of S. sclerotiorum isolates make difficult the selection of resistant genotypes (CARNEIRO et al, 2011;PASCUAL et al, 2010;SCHWARTZ and SINGH, 2013;SILVA et al, 2014). Although, some papers report a small variability of this pathogen in Brazil (LEHNER et al, 2015;LEHNER et al, 2016 a).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some researchers have been working to increase the level of white mold resistance in common bean cultivars (LYON et al 1987;SINGH, 2009;SINGH, 2010;LEITE et al, 2016). It has already been identified lines with similar resistance to non-adapted sources in Brazil (GONÇALVES; SANTOS, 2010;LEITE et al, 2016;SILVA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%